WORK PRACTICE AS A METHOD OF DEVELOPMENT OF CREATIVE INDIVIDUALITY OF FUTURE PLUMBERS - ELECTRICIANS - Igor Roskvas (Vasyl Stefanyk Precarpathian National University, 2018)
The article presents the development of creative individuality of future plumbers - electricians who are studying in vocational schools during the internship. Analyzed the concept, purpose and effectiveness of manufacturing practices. Considered professional qualities of future skilled workers, which should be formed for the purpose of development of creative individuality. Studied and researched practical techniques for development of creativity. In addition, the emphasis on the value of independent work of future specialists for the development of their artistic personality. Key words: individuality, creativity, creative personality, development, creative activities, practical training, independent work, future mechanic - electrician, professional Lyceum.